2018
DOI: 10.1186/s12917-018-1361-z
|View full text |Cite
|
Sign up to set email alerts
|

The serostatus of Brucella spp., Chlamydia abortus, Coxiella burnetii and Neospora caninum in cattle in three cantons in Bosnia and Herzegovina

Abstract: BackgroundDairy production in Bosnia and Herzegovina exhibits limited productivity, which may partly, be explained by extensive reproductive problems of non-infectious and infectious origin. Brucella spp., Chlamydia abortus, Coxiella burnetii and Neospora caninum are common infectious causes of decreased reproductive outcomes in cattle worldwide. Little is, however, known about the disease status of herds with reduced reproductive performances. A cross-sectional study was designed to document the status of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…Although serological evidence of exposure to C. burnetii has already been reported in cattle in Europe (CZAPLICKI et al, 2009;AGGER et al, 2010;BOTTCHER et al, 2011;GACHE et al, 2017;RYAN et al, 2018;VARELA-CASTRO et al, 2018;VIDAL et al, 2017;SOFTIC et al, 2018), Asia (CETINKAYA et al, 2000NOKHODIAN et al, 2016), North America (MCQUISTON et al, 2005 and Africa (KAMGA-WALADJO et al, 2010;SCOLAMACCHIA et al, 2010), there are few data on seroprevalence to this agent in ruminants in Brazil. In this regard, while Guimarães et al (2017) found a seropositivity rate of 2% for C. burnetii among sheep sampled in the state of Piauí, northeast of Brazil, Oliveira et al (2018) found a seroprevalence of 55.1% in a herd of goats with history of reproductive disorders in the state of Alagoas, Northeast of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Although serological evidence of exposure to C. burnetii has already been reported in cattle in Europe (CZAPLICKI et al, 2009;AGGER et al, 2010;BOTTCHER et al, 2011;GACHE et al, 2017;RYAN et al, 2018;VARELA-CASTRO et al, 2018;VIDAL et al, 2017;SOFTIC et al, 2018), Asia (CETINKAYA et al, 2000NOKHODIAN et al, 2016), North America (MCQUISTON et al, 2005 and Africa (KAMGA-WALADJO et al, 2010;SCOLAMACCHIA et al, 2010), there are few data on seroprevalence to this agent in ruminants in Brazil. In this regard, while Guimarães et al (2017) found a seropositivity rate of 2% for C. burnetii among sheep sampled in the state of Piauí, northeast of Brazil, Oliveira et al (2018) found a seroprevalence of 55.1% in a herd of goats with history of reproductive disorders in the state of Alagoas, Northeast of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Elkjaer et al reported that even mild uterine infection could have an adverse effect on CFI [37]. Similarly, the uterine infection was also one of the observations associated with poor reproductive performance as presented in an earlier paper by our group [13]. e calving interval (CI) was calculated as the traditionally used fertility indicator, and the median CI of 385 days indicates a relatively good reproductive performance in selected dairy farms in Una-Sana Canton.…”
mentioning
confidence: 82%
“…Since there was no complete list of all dairy farms in Una-Sana Canton, the sampling frame consisted of dairy farms from the available municipal lists of cooperatives with dairies. In addition, the selection of farms was based on a subset of dairy farms assembled retrospectively from a previous study on farm management and reproductive infections in dairy cattle, as described in [13]. e general inclusion criterion was the existence of an on-farm written recording system for reproductive data at the individual animal level.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Databases and statistical analyses 174 The questionnaire data were entered into a Microsoft Excel ® spreadsheet before inspected and 175 merged with data from the previously reported serological survey (Softic et al, 2018) were screened for their influence on abortion, stillbirths, retained placenta and metritis, as well 183 as, infectious agents. As all reproduction and infection outcomes were coded as present/ absent 184 (seropositive/ seronegative herd), a mixed-effects univariable logistic regression was used to 185 screen management factors for potential statistical influence.…”
mentioning
confidence: 99%